From birth to weaning: maternal investment, cub development and behaviour in Sumatran tigers (Panthera tigris sumatrae) - Naidenov, Laura; Grindle, Chris; Duke, Jonathon; Gough, Elena J.; Davis, Nick; Hall, Dave; Waterman, James O.; Holmes, Lisa (Frontiers in Conservation Science, 2024)
The modern zoo relies on the persistence of genetically and physiologically healthy populations of endangered species, which is enabled through breeding programs globally and regionally. Many species commonly held in zoos are poorly studied in the wild, leading to a lack of in-depth knowledge surrounding breeding behaviours and subsequent parental behaviours and early life development of young. Knowledge of this information is critical to make informed management decisions which promote successful rearing of young in zoos. While the critically endangered Sumatran tiger is popular in zoos, rates of cub survival in the first 5 months are lower than 50%, highlighting the need for scientific evidence driving management decisions. This study monitors nursing and cub grooming behaviours in a first-time mother Sumatran tiger (Panthera tigris sumatrae) and her cubs throughout four stages of cub development. The social proximity of cubs and dam were recorded to describe social interactions within the group throughout cub aging. A series of Friedman tests and post-hoc tests found significant decreases in both cub grooming (χ2 (3, N = 96) = 14.20, p < 0.01) and nursing (χ2 (3, N = 96) = 25.77, p < 0.001) behaviours between the birth and weaning of the cubs, as well as within different phases of cub development between those times. Cub-to-cub proximity was maintained from birth to weaning, with cubs spending significant amounts of time in close proximity (within one adult body length) of each other (χ2 (3, N = 96) = 15.231, p = 0.001) throughout the study. The dam was found to spend significantly less time with the cubs as they reached weaning age (χ2 (3, N = 96) = 27.88, p < 0.001). These results are thought to be the first of their kind to detail timings of cub development and early life socialisation, providing evidence for timing of first food provision to young and promote the provision of space for the dam to spend time away from the cubs, while allowing the cubs to become confident, mobile, and independent.